Osteoprotegerin as an Emerging Biomarker of Carotid Artery Stenosis? A Scoping Review with Meta-Analysis - Jerzy Chudek; Marta Pośpiech; Anna Chudek; Michał Holecki; Monika Puzianowska-Kuźnicka (Diagnostics)
Objective: In developed countries, stroke is the fifth cause of death, with a high mortality rate, and with recovery to normal neurological function in one-third of survivors. Atherosclerotic occlusive disease of the extracranial part of the internal carotid artery and related embolic complications are common preventable causes of ischemic stroke (IS), attributable to 7–18% of all first-time cases. Osteoprotegerin (OPG), a soluble member of the tumor necrosis factor receptor (TNFR) superfamily, is considered a modulator of vascular calcification linked to vascular smooth muscle cell proliferation and collagen production in atherosclerotic plaques. Therefore, OPG emerges as a potential biomarker (BM) of calcified carotid plaques and carotid artery stenosis (CAS). Methods: We performed a literature search of PubMed on OPG in CAS and atherosclerosis published until 2024. Results: Increased levels of serum OPG were reported in both patients with symptomatic and asymptomatic CAS, and higher values were observed in those with unstable atherosclerotic plaques. Notably, increased OPG levels were observed regardless of the location of atherosclerosis, including coronary and other peripheral arteries. In addition, chronic kidney disease, the most significant confounder disturbing the association between vascular damage and circulating OPG levels, decreases the usefulness of OPG as a BM in CAS. Conclusions: Osteoprotegerin may be considered an emerging BM of global rather than cerebrovascular atherosclerosis. Its diagnostic significance in identifying patients with asymptomatic CAS and their monitoring is limited.